2004
DOI: 10.1016/s0002-9440(10)63295-6
|View full text |Cite
|
Sign up to set email alerts
|

Mostly Separate Distributions of CLAC- versus Aβ40- or Thioflavin S-Reactivities in Senile Plaques Reveal Two Distinct Subpopulations of β-Amyloid Deposits

Abstract: Collagenous Alzheimer amyloid plaque component (CLAC) is a unique non-Abeta amyloid component of senile plaques (SP) derived from a transmembrane collagen termed CLAC-precursor. Here we characterize the chronological and spatial relationship of CLAC with other features of SP amyloid in the brains of patients with Alzheimer's disease (AD), Down syndrome (DS), and of PSAPP transgenic mice. In AD and DS cerebral cortex, CLAC invariably colocalized with Abeta42 but often lacked Abeta40- or thioflavin S (thioS)-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…DAEFRHDS-GYE) that may interact with positive charges on CLAC. Our recent immunohistochemical analysis of postmortem brains from patients with AD or Down's syndrome showed that CLAC is a relatively early component of senile plaque amyloid coexisting with A␤42, whereas deposition of A␤40 occurs chiefly in CLAC-negative senile plaques at a later stage (17). This apparently suggested that CLAC may have different affinities to A␤42 and A␤40.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DAEFRHDS-GYE) that may interact with positive charges on CLAC. Our recent immunohistochemical analysis of postmortem brains from patients with AD or Down's syndrome showed that CLAC is a relatively early component of senile plaque amyloid coexisting with A␤42, whereas deposition of A␤40 occurs chiefly in CLAC-negative senile plaques at a later stage (17). This apparently suggested that CLAC may have different affinities to A␤42 and A␤40.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the ectodomain of CLAC-P is shed by furin convertase and secreted as a soluble form of CLAC (sCLAC) (15). Immunohistochemical analysis of postmortem human brains revealed a unique pattern of CLAC deposition in AD and Down's syndrome brains (17); CLAC was negative in A␤42-positive, A␤40-negative pure diffuse plaques that are considered to be the earliest form of A␤ deposition, whereas a fraction of primitive-type senile plaques became CLAC-positive at a relatively early stage of plaque maturation as the fibrillization of A␤ progresses. Notably, mature plaques that appear at later stages were A␤40/thioflavin S-positive but remained CLAC-negative (17).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Thioflavin S (ThS) has been applied to some extent, but mainly for diagnosis of amyloid fibril deposits in tissue sections using fluorescence microscopy [61,62]. ThS is less suitable for kinetics analysis than ThT since free ThS fluorescence interferes significantly with the determination of the fibrilbound species [40,46].…”
Section: Overview Of Molecular Probes For Amyloid Fibril Detectionmentioning
confidence: 99%
“…Radioactively labelled [55,56] PTAA Fluorescence [57] Resveratrol Fluorescence [58] SH-516 Fluorescence [59][60][61] T-284 Fluorescence [59,61] Thiazin red Fluorescence [62] Thioflavin S* Fluorescence [63,64] Thioflavin T Fluorescence [65,66] X-34 Fluorescence [67] *Mixture of planar asymmetric dyes with charged group at the end of the molecule.…”
Section: Overview Of Molecular Probes For Amyloid Fibril Detectionmentioning
confidence: 99%